Relationship Between Individual Characteristics And Level Of Knowledge With The Risk Of Marriage Of Parents To Children - Yulianti, Yulianti (Jurnal MIDPRO, 2023)
Violence against children is all forms of action or treatment that hurts physically or emotionally, sexual abuse, neglect, commercial exploitation or other exploitation, which results in actual or potential injury or loss to the child's health, child survival, child development or child dignity, which done in the context of a relationship of responsibility. This study uses a quantitative research method through a cross sectional approach which aims to determine the relationship between individual characteristics and level of knowledge on the impact of violence on school-age children and parental marriage in Nambo Village. The population participating in the study were all women of childbearing age in Nambo Village, Klapanunggal District, Bogor Regency. The sample used in this study was 84 women of childbearing age using purposive sampling technique. Data analysis used in this study is bivariate and multivariate analysis. The results of the study showed that there was a relationship between the age of the mother's marriage and the risk of violence in children with the mother's education with a P-value = 0.000. There is a relationship between the age of the mother's marriage to the risk of violence in children with the mother's knowledge with P-value = 0.000. The results of the multivariate analysis showed that the mother's education variable was the strongest factor in influencing the risk of violence in children with a P-value = 0.000. Suggestions that can be submitted to be able to prevent the risk of violence in children health workers can work together with agencies in the community to provide counseling and assistance to be able to create welfare for the growth and development of children by preventing the risk of violence in children.Â